Dinâmica hidrológica do trecho inferior do Rio Cauamé, em Boa Vista/RR - Magalhães, Rômulo Ferreira de (Universidade Federal de Roraima, 2022)
This scientific work proposed a hydrological analysis from the installation of a fluviopluviometric research station, in the lower Cauamé River, in the city of Boa Vista, which did not have an automatic hydrological monitoring station until March 2019. Knowledge of the hydrological behavior it was restricted in this hydrographic basin, due to the lack of hydrometeorological monitoring stations in the area, which hindered the work of diagnosing and forecasting the use of its water resources. The research methodology included recognition, selection and field installation of the monitoring station, which was inspected in 12 technical visits; the selection of monitoring stations in bordering basins, to compare the results with the station in the study area; the analysis and statistical treatment of acquired data, both at the research station and at the comparative stations and; interpretation of results. The analyzes carried out from the data acquired at the monitoring station in Fazenda Recreio showed that the hydrological behavior of the lower Cauamé river basin follows the trend of the main river system, which is Branco-Uraricoera, also showing that the hydrological behavior of the lower Cauamé river it is congruent with the other basins in the period of drought, flood, water level amplitude and median monthly quotas. The average annual flow, the reference flows and the analyzes made from the net discharge values of the lower Cauamé river, at the extinct Sítio Jaraguá station, between 2003 and 2009, made it possible to determine the Q50 flow rates, of 81.5m³ / s; Q90, of 17.9m³ / s; Q95, 7.33m³ / s and; Q7.10, of 3.21m³ / s. The 6 rainiest months in the lower Cauamé River were from May / 2019 to September / 2019, together with the month of November / 2019. It was found that the least rainy months in all seasons were October / 2019, December / 2019, January / 2020, February / 2020 and March / 2020. The rainy period represented 89.15% of the accumulated total and the drought period represented 10.85% of the total. The comparison of the daily precipitation results of Fazenda Recreio and other comparative stations showed congruence given by the high and positive coefficient of determination, R² = 0.89. These results can be further improved by maintaining the Fazenda Recreio station and assisting in the studies of future projects that require the granting of the right to use water in the Cauamé River.